2008
DOI: 10.1590/s0034-89102008005000005
|View full text |Cite
|
Sign up to set email alerts
|

Diferenças socioeconômicas entre autoclassificação e heteroclassificação de cor/raça

Abstract: OBJECTIVE: To assess (1) the consistency between self-classifi ed and interviewer-classifi ed color/race according to socioeconomic and demographic variables and (2) the magnitude of the ethnic-racial inequalities of income and socioeconomic status using self-classifi ed and interviewer-classifi ed color/race. METHODS:A cross-sectional population-based study was carried out among individuals of both sexes aged >20 years (N=3,353), living in the urban area of a city in Southern Brazil, in 2005. A two-stage samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
1
2
0
2
Order By: Relevance
“…The main limitations of this study are the absence of information on race in 3.6% of deaths from oral cancer during the study period, and the use of two different frameworks to assess race; i.e., classifi cation by health professionals in death certifi cates, and self-reported classifi cation at the population level. 7 We also observe that studies in the Brazilian context concluded that self-reported race depends on racial features of the interviewer. 8 Sao Paulo has been reported to have a system of information on mortality as accurate as any other country with a long tradition in the area of health statistics, 17 and we are unaware of variations in the quality of death certifi cates by race in the short term.…”
Section: Discussionsupporting
confidence: 53%
“…The main limitations of this study are the absence of information on race in 3.6% of deaths from oral cancer during the study period, and the use of two different frameworks to assess race; i.e., classifi cation by health professionals in death certifi cates, and self-reported classifi cation at the population level. 7 We also observe that studies in the Brazilian context concluded that self-reported race depends on racial features of the interviewer. 8 Sao Paulo has been reported to have a system of information on mortality as accurate as any other country with a long tradition in the area of health statistics, 17 and we are unaware of variations in the quality of death certifi cates by race in the short term.…”
Section: Discussionsupporting
confidence: 53%
“…Besides, non-white individuals presented more chances of not accessing the medicines, as demonstrated in other studies 12 . These results not only reflect the worse socioeconomic conditions of this group 27 , but also shows the lower access to health 28 . In this sense, Boing et al (2013) 10 highlighted the importance of SUS to promote health, once it increases the access to medication for underprivileged groups.…”
Section: Discussionmentioning
confidence: 82%
“…Research on the Brazilian population shows that brown and black skinned individuals, generally, have lower income than those with white skin, even taking other socioeconomic and demographic factors such as schooling, sex, and age into account. 2,22 In this study, the difference observed regarding skin color, may be an important indicator of socioeconomic inequalities because brown and black skinned individuals are still placed at the bottom of the social ladder in Brazil.…”
Section: Discussionmentioning
confidence: 86%